THE INFLUENCE OF DIGITAL LITERACY, SELF-EFFICACY AND INCOME EXPECTATIONS ON THE INTEREST IN ENTREPRENEURSHIP IN STUDENTS OF THE FACULTY OF ECONOMICS, STATE UNIVERSITY OF JAKARTA CLASS OF 2017: PENGARUH LITERASI DIGITAL, EFIKASI DIRI DAN EKSPEKTASI PENDAPATAN TERHADAP MINAT BERWIRAUSAHA PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS NEGERI JAKARTA ANGKATAN 2017 - Nur Haliza (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2022)
This study aims to analyze the effect of digital literacy, self-efficacy and income expectations on entrepreneurship interest on the students of faculty of economics 2017, State University of Jakarta. The method used in this research is descriptive quantitative. The population reached in this study were all faculty of economics students 2017 at State University of Jakarta and the sample was 223 students. The sampling technique is proportional stratified random sampling. Data was collected using questionnaires or questionnaires distributed via google forms to 223 students of the faculty of economics, State University of Jakarta. The data analysis technique used is path analysis. This study reveals that: 1) digital literacy has a positive and significant effect of 20.5% on entrepreneurship interest, 2) self-efficacy has a positive and significant effect of 25.8% on entrepreneurship interest, 3) income expectations has a positive and significant effect on 45.6% on entrepreneurship interest, 4) digital literacy, self-efficacy and income expectations together have a positive and significant effect of 55.6% and the rest are influenced by other factors